2002
DOI: 10.1177/0049124102031002003
|View full text |Cite
|
Sign up to set email alerts
|

Studying Rare Events Through Qualitative Case Studies

Abstract: This article considers five methodological challenges in studying rare events such as school shootings. Drawing on the literature on causal analysis in macro-historical and other small-N research, it outlines strategies for studying school shootings using qualitative case studies and illustrates these strategies using data from case studies of two rampage school shootings: Heath High School in West Paducah, Kentucky, and Westside Middle School outside Jonesboro, Arkansas. Strengths and limitations are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…Although I consider my findings to be generalizable to some extent, the contribution of this study is limited in the way typical of explorative research (Harding et al, 2002). First, I did not gather any ethnographic data during the outbreak, which might have explained how reducing and inducing uncertainty relate to one another (e.g., in the case of hospitals).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although I consider my findings to be generalizable to some extent, the contribution of this study is limited in the way typical of explorative research (Harding et al, 2002). First, I did not gather any ethnographic data during the outbreak, which might have explained how reducing and inducing uncertainty relate to one another (e.g., in the case of hospitals).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, restrictions concerning data access as well as ethical and juridical issues further limit the insights gained and information available for analysis. Although this restriction applies to crisis or disaster research in general (Harding et al, 2002), it held particularly true for this study given that lawsuits regarding the EHEC outbreak and norovirus cases are ongoing at the time of writing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the prevalence of homicide among school-age children occurring at school is relatively low (<1%, Harding, Fox, & Mehta, 2002;Kachur et al, 1996), there is an increased effort to identify and refer potentially problematic students for mental health counseling (Mulvey & Cauffman, 2001). Faculty and staff indicated that faculty should be alert to student behavior and provide referrals and support for students in need.…”
Section: Discussionmentioning
confidence: 99%
“…Columbine High School shooting). Historically, one of the largest obstacles in studying this type of school shootings is the case definition problem (Harding, Fox, and Mehta, 2002).…”
Section: Rampage School Shootingsmentioning
confidence: 99%